Escaping the Great Recession - Bianchi, Francesco; Melosi, Leonardo (American Economic Review, 2017)
We show that policy uncertainty about how the rising public debt will be stabilized accounts for the lack of deflation in the US economy at the zero lower bound. We first estimate a Markov-switching VAR to highlight that a zero-lower-bound regime captures most of the comovements during the Great Recession: a deep recession, no deflation, and large fiscal imbalances. We then show that a microfounded model that features policy uncertainty accounts for these stylized facts. Finally, we highlight that policy uncertainty arises at the zero lower bound because of a trade-off between mitigating the recession and preserving long-run macroeconomic stability. (JEL E31, E32, E52, E62, G01, H63)